Peningkatan Hasil Belajar IPAS Melalui Penerapan Model Pembelajaran Problem Based Learning (PBL) Tentang Pemahaman Sifat-Sifat Cahaya Pada Kelas V SDN 241 Palembang - Meise Nurul Utami; Yenny Anwar; Nur Fitrah Dewi (JOURNAL SAINS STUDENT RESEARCH, 2025)
This Problem Based Learning (PBL) learning model is a learning model that invites students to identify and solve real problems that can increase student engagement and motivation to learn. The purpose of the study is for students to collaborate in groups to explore knowledge, thereby strengthening critical thinking skills and problem-solving abilities. The results of this study indicate that the problem based learning model can help students in the learning process to understand the properties of light. From the results of the study, it can be concluded that the problem based learning model has an influence on increasing student participation, especially in science subjects. This learning model focuses on the process and the end result and how students solve problems so that they can produce a problem solving or product. So this learning model is appropriate for use in science learning and the Merdeka curriculum which prioritizes student-centered learning.